2006
DOI: 10.1182/blood-2006-10-049312
|View full text |Cite
|
Sign up to set email alerts
|

In vivo administration of lentiviral vectors triggers a type I interferon response that restricts hepatocyte gene transfer and promotes vector clearance

Abstract: Liver gene transfer is a highly sought goal for the treatment of inherited and infectious diseases. Lentiviral vectors (LVs) have many desirable properties for hepatocyte-directed gene delivery, including the ability to integrate into nondividing cells. Unfortunately, upon systemic administration, LV transduces hepatocytes relatively inefficiently compared with nonparenchymal cells, and the duration of transgene expression is often limited by immune responses. Here, we investigated the role of innate antiviral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
150
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(162 citation statements)
references
References 49 publications
10
150
2
Order By: Relevance
“…However, pDCs were potently activated by HIV particles and produced type I IFN which induced the bystander maturation of myeloid DCs. Brown et al confirmed this finding in vivo showing that the lentivector could activate pDC to generate type I IFN which may limit transgene expression 56 . Thus, it seems that lentivector can activate pDC which could then indirectly activate myeloid CD11c+ DCs.…”
Section: Transduction Of Apcs With Recombinant Lentivectorsupporting
confidence: 70%
“…However, pDCs were potently activated by HIV particles and produced type I IFN which induced the bystander maturation of myeloid DCs. Brown et al confirmed this finding in vivo showing that the lentivector could activate pDC to generate type I IFN which may limit transgene expression 56 . Thus, it seems that lentivector can activate pDC which could then indirectly activate myeloid CD11c+ DCs.…”
Section: Transduction Of Apcs With Recombinant Lentivectorsupporting
confidence: 70%
“…However, the activation of conventional DC in vivo hasto our knowledge -not been studied. In contrast, a role for pDC on in vivo administration of lentiviral vectors has been suggested by Brown et al 122 They show that administration of lentiviral vectors to mice triggers a rapid and transient type I IFN response. The observed effect was independent of the envelope pseudotype, but dependent on functional vector particles, suggesting the necessity of cell entry.…”
Section: Immunogenicity Of Lentiviral Vectorsmentioning
confidence: 91%
“…A key obstacle of stem cell-based gene therapy is the lack of safe and effective gene delivery systems. Viral vectors are the current gold standard for achieving high gene delivery efficiency into various human stem cells (27)(28)(29), but the broad clinical applications are limited by potential immune responses and unintended genomic integration events (21,22). Here, we report a safe and efficient method for transducing hADSCs with a full-length TRAIL using hydrolysable polymeric nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…A recombinant soluble version of the transmembrane death ligand TRAIL has shown compelling preclinical results as a potential cancer therapeutic agent, but only rare clinical responses have been observed in clinical trials, possibly because of insufficient tumor exposure (17,18) and/or weak engagement of the extrinsic pathway (19,20). On the contrary, in the case of viralmediated TRAIL gene therapy, limitations arise from triggering immune responses and unintended genomic integration events (21,22), which remain a key bottleneck for broad clinical application.…”
mentioning
confidence: 99%